Supporting multilingual learners’ reading competence: a multiple case study of teachers’ instruction and student learning and motivation - Gallagher, Melissa A.; Beck, Jori S.; Ramirez, Erin M.; Barber, Ana Taboada; Buehl, Michelle M. (Frontiers in Education, 2023)
Supporting students' reading competence (i.e., their comprehension and vocabulary) is complex, particularly when working with multilingual learners, and involves implementing instructional practices to support their behavioral engagement in reading as well as their reading motivation. The purpose of this mixed methods case study was to examine changes in multilingual learners' reading comprehension, academic vocabulary, reading engagement, and reading motivation after participating in a 7-week intervention called United States History for Engaged Reading (USHER) and then examine qualitative data to explain why these changes may have occurred. We found changes in the reading comprehension of MLs across all four teachers' classes, and variable changes in academic vocabulary, reading engagement, and reading motivation. We highlight specific instructional practices that may have led to these changes, including engaging students in discussions during explicit vocabulary instruction, allowing students choice and the opportunity to collaborate, and making the content relevant by relating it to students' lives, among others. and is predicted by students' motivation (Taboada Barber et al.